Aerodynamic and structural design of a 2022 Formula One front wing assembly - Castro, Xabier; Rana, Zeeshan A. (MDPI, 2020)
The aerodynamic loads generated in a wing are critical in its structural design. When multi-element wings with wingtip devices are selected, it is essential to identify and to quantify their structural behaviour to avoid undesirable deformations which degrade the aerodynamic performance. This research investigates these questions using numerical methods (Computational Fluid Dynamics and Finite Elements Analysis), employing exhaustive validation methods to ensure the accuracy of the results and to assess their uncertainty. Firstly, a thorough investigation of four baseline configurations is carried out, employing Reynolds Averaged Navier–Stokes equations and the k-ω SST (Shear Stress Transport) turbulence model to analyse and quantify the most important aerodynamic and structural parameters. Several structural configurations are analysed, including different materials (metal alloys and two designed fibre-reinforced composites). A 2022 front wing is designed based on a bidimensional three-element wing adapted to the 2022 FIA Formula One regulations and its structural components are selected based on a sensitivity analysis of the previous results. The outcome is a high-rigidity-weight wing which satisfies the technical regulations and lies under the maximum deformation established before the analysis. Additionally, the superposition principle is proven to be an excellent method to carry out high-performance structural designs.
Keywords: aerodynamics; structural design; Formula One; wing; structural deformation